2015
DOI: 10.1152/ajpregu.00056.2015
|View full text |Cite
|
Sign up to set email alerts
|

Sugar-induced cephalic-phase insulin release is mediated by a T1r2+T1r3-independent taste transduction pathway in mice

Abstract: Sensory stimulation from foods elicits cephalic phase responses, which facilitate digestion and nutrient assimilation. One such response, cephalic-phase insulin release (CPIR), enhances glucose tolerance. Little is known about the chemosensory mechanisms that activate CPIR. We studied the contribution of the sweet taste receptor (T1r2+T1r3) to sugar-induced CPIR in C57BL/6 (B6) and T1r3 knockout (KO) mice. First, we measured insulin release and glucose tolerance following oral (i.e., normal ingestion) or intra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
67
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 58 publications
4
67
0
Order By: Relevance
“…In addition to a purely sensory role, the T1R-independent pathway may also have a role in regulating metabolism. Indeed, a robust cephalic phase insulin release (CPIR) can be induced by oral administration of glucose or sucrose, but not fructose in WT and Tas1r3 KO mice (36). The CPIR improved glucose tolerance in both strains, buttressing the physiological importance of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to a purely sensory role, the T1R-independent pathway may also have a role in regulating metabolism. Indeed, a robust cephalic phase insulin release (CPIR) can be induced by oral administration of glucose or sucrose, but not fructose in WT and Tas1r3 KO mice (36). The CPIR improved glucose tolerance in both strains, buttressing the physiological importance of this pathway.…”
Section: Resultsmentioning
confidence: 99%
“…Insulin release from the pancreas may also be stimulated by glucagon-like peptide 1 (GLP1; also known as incretin), which is secreted by sweet-sensing taste bud cells 30, 31 . Sugar-induced CPIR persists in Tas1r3 -knockout mice 32 and is mediated through the action of KATP channels 33 . Thus, at least two distinct and parallel sugar-sensing mechanisms seem to be initiated in taste buds: one that signals the perception of carbohydrate-rich foods (that is, sweet tastes, via T1R2–T1R3) and one that deploys a physiological reflex of insulin secretion (via a transporter).…”
Section: Chemosensory Transductionmentioning
confidence: 99%
“…In humans and animals, saccharides elicit CPIR [45][46][47] . Although this might suggest that CPIR is mediated by T1Rs, the sensory mechanisms underlying CPIR are unclear.…”
Section: Taste Perception Primes Regulatory Physiologymentioning
confidence: 99%
“…HPS do not reliably elicit cephalic phase responses, which suggests that CPIR may be mediated by T1R-independent carbohydrate detection in the oral cavity [48][49][50] . More recently, it was shown that oral stimulation with glucose stimulates CPIR in T1R knockout animals [46] . And fructose, which does not bind SGLT1, fails to stimulate CPIR.…”
Section: Taste Perception Primes Regulatory Physiologymentioning
confidence: 99%